Primary Nasal Neuroendocrine Tumor: Rare Case Report - Bandhate, Kamal; Diwan, Ashok Kumar; Mahobia, Vijay (Asian Journal of Medical Research, 2021)
Nasal cavity small cell neuroendocrine tumor is an exceptionally rare and violent tumor. The tumor carries a poor prognosis in spite of active treatment, with a high risk of local recurrence and distant metastases. Platinum-based chemotherapy combined with radiotherapy is used in the treatment of small cell cancer. We have a rare case of neuroendocrine primary nasal carcinoma. A 62-year-old female patient comes to OPD with a history of Epistaxis from the left nostril and watering from the left eye.